Translating Wordplay: A case study on the translation of wordplay in Terry Pratchett’s Soul Music - Mustonen, Marjo (My University, 2016)
Wordplay and the translation of wordplay is a complex subject that has been addressed by various studies. The combination of a single form and multiple meanings created by wordplay makes it challenging to translate. Translating wordplay has even been considered impossible. This thesis explores wordplay and the translation of wordplay through an analysis of wordplay found in an English novel and its Finnish translation. The purpose is to shed light on the problems and solutions found in the data. The study consists of a quantitative analysis and a subsequent discussion on the findings. The findings from the study indicate that cultural aspects such as idioms and allusions are especially problematic when it comes to translating wordplay. Also, the communicative functions of wordplay were found to be central for a successful translation. It is concluded that these aspects require further study.